Studi Penghematan Biaya Dengan Konsep Pengalihan Kendaraan Pribadi Ke Kendaraan Online Di Kota Harapan Indah Bekasi - Nasrullah, Nasrullah (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The requirement for a smooth and decent vehicle is naturally the single longing of all metropolitan networks in Indonesia. To solve transportation problems, individuals will generally purchase their own vehicles as motor vehicles and automobiles. This is due to the disappointment of vehicle users towards public transport. This condition brings about the expansion of vehicle ownership, bringing the development of the quantity of vehicles that are not similar to the road foundation, so it tends to clog for a very long time. This research is expected to be a solution or input for vehicle user savings. The study centers on interview surveys and recently led polls on online vehicle clients and confidential vehicle administration and private vehicle owners, under the condition of planned diversion to online application vehic. compiling questionnaires using the Multi Regression analysis method with the SPSS16.0 computer program which is used systematically to draw conclusions, For utilization below 21 km every day, online vehicle determination is cheaper than private vehicles, actually for use more than 21 km every day, the choice of secret vehicles is cheaper than online vehicles